The Conventional Technique Versus the No-touch Isolation Technique for Primary Tumor Resection in Patients With Colon Cancer (JCOG1006): A Multicenter, Open-label, Randomized, Phase III Trial. Issue 5 (18th May 2022) - Takii, Yasumasa; Mizusawa, Junki; Kanemitsu, Yukihide; Komori, Koji; Shiozawa, Manabu; Ohue, Masayuki; Ikeda, Satoshi; Takiguchi, Nobuhiro; Kobatake, Takaya; Ike, Hideyuki; Sato, Toshihiko; Tomita, Naohiro; et al.
Abstract : Objective: This phase III trial evaluated whether the no touch was superior to the conventional in patients with cT3/T4 colon cancer. Background: No touch involves ligating blood vessels that feed the primary tumor to limit cancer cell spreading. However, previous studies did not confirm the efficacy of the no touch. Methods: This open-label, randomized, phase III trial was conducted at 30 Japanese centers. The eligibility criteria were histologically proven colon cancer; clinical classification of T3–4, N0–2, andM0; and patients aged 20 to 80years. Patients were randomized (1:1) to undergo open surgery with conventional or the no touch. Patients with pathological stage III disease received adjuvant capecitabine chemotherapy. The primary endpoint was disease-free survival (DFS) according to the intention-to-treat principle. Results: Between January 2011 and November 2015, 853 patients were randomized to the conventional group (427 patients) or the no touch group (426 patients). The 3-year DFS were 77.3% [95% confidence interval (CI) 73.1%–81.0%] and 76.2% (95% CI 71.9%–80.0%) in the conventional and no touch groups, respectively. The superiority of no touch was not confirmed: hazard ratio for DFS = 1.029 (95% CI 0.800– 1.324; 1-sided P = 0.59). Operative morbidity was observed in 31 of 427 conventional patients (7%) and 26 of 426 no touch patients (6%). All grade adverse events were similar between the conventional and no touch groups. No in-hospital mortality occurred in either group. Conclusion: The present study failed to confirm the superiority of the no touch.